2012
DOI: 10.1158/1940-6207.capr-11-0460
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Malignant Melanoma in White and Non-White/Non–African American Populations: The Multiethnic Cohort

Abstract: It is unknown whether the established risk factors for malignant melanoma in whites influence malignant melanoma risk in non-whites. We examined the risk factors for melanoma among 39,325 whites and 101,229 non-whites/multiracials (Japanese American [47.5%], Latino American [34.8%], Native Hawaiian [2.1%] and multiracial [15.6%], excluding African Americans) in the Multiethnic Cohort study. With an average follow-up of 12.7 years, 581 invasive malignant melanoma (IMM) and 412 melanoma in situ (MIS) cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 54 publications
1
35
0
1
Order By: Relevance
“…While SES has an established relationship with melanoma, three U.S. studies and two international studies provide grade B evidence that high SES and melanoma incidence may be unrelated . An Australian study published in 2011 notes that areas of disadvantage had higher incidence of melanoma among women only .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While SES has an established relationship with melanoma, three U.S. studies and two international studies provide grade B evidence that high SES and melanoma incidence may be unrelated . An Australian study published in 2011 notes that areas of disadvantage had higher incidence of melanoma among women only .…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][15][16][17][18][19][20][21][22]24,25,[27][28][29][30][31][32][33][34]37 While SES has an established relationship with melanoma, three U.S. studies and two international studies provide grade B evidence that high SES and melanoma incidence may be unrelated. 12,14,23,39,40 An Australian study published in 2011 notes that areas of disadvantage had higher incidence of melanoma among women only. 13 Of note, a Canadian study from 2007 observed that higher SES populations have higher incidence; however, rural environments also have higher incidence.…”
Section: Incidencementioning
confidence: 99%
“…6. The C43 incidence rates vary between geographical areas, with the highest rates in Europe [33,51,62] and in countries with the greatest proportion of European descendants [6,11,[63][64][65]. Therefore, we have constructed the following two further variables concerning populations of European origin/ descendants.…”
Section: As Per the International Statistical Classi Cation Of Diseasmentioning
confidence: 99%
“…11,17,18 A limited number of studies have confirmed some of these risk factors in non-white populations. 16,17 Risk factors for melanoma have not been explored in the AIAN population specifically, although possible risk factors may be gleaned from previous studies. Wu et al showed that rates of melanoma increased with age and were higher for males in the AIAN population, as for all other racial groups.…”
Section: Cutaneous Oncologymentioning
confidence: 99%